Etnomusiklopedia: A Comprehensive Digitization Model for Preserving Indonesia’s Musical Heritage - Aryandari, Citra; Nurvijayanto, Ribeth; Manurung, Sopandu (Perpustakaan dan Arsip Universitas Gadjah Mada, 2026)
Indonesia's ethnomusicological heritage, documented since Jaap Kunst's early 20th-century works, remains largely inaccessible due to fragmented archival systems and analog-based documentation. This research addresses the